Effect of temperature and morphology on the electrical properties of PET/conductive nanofillers composites. (15th February 2018) - Gorrasi, Giuliana; Bugatti, Valeria; Milone, Candida; Mastronardo, Emanuela; Piperopoulos, Elpida; Iemmo, Laura; Di Bartolomeo, Antonio
Abstract: Poly(ethylene terephthalate) (PET) composites were loaded with four different carbon-based fillers: functionalized carbon nanotubes (CNT), exfoliated graphite (EG), and hybrid materials such as Mg(OH)2, which is primarily used as a flame retardant additive in plastics, dispersed over functionalized CNT and EG. The technology used to mix the different phases was high energy ball milling in dry conditions and at ambient temperature. Morphological organization, thermal and electrical properties of composites were evaluated and correlated with the type of filler. The electrical properties were analyzed over a wide temperature range, from 25 °C to 150 °C, and correlated to the starting structural organization of the composites and the morphological transformations occurred during the thermal heating. The addition of EG and CNTs to PET did not have influence on the amorphous arrangement of unfilled PET, while the loading of Mg(OH)2 /EG and Mg(OH)2 /CNT fillers favoured the PET crystallization. The crystallization inducted by temperature allowed an increasing in electrical conductivity of the starting amorphous samples. On the other hand, it was found a conductivity independent of temperature for semicrystalline samples (filled with Mg(OH)2 /EG and Mg(OH)2 /CNT). The charge transport, for the analyzed PET composites, is favoured by the higher degree of crystallinity.